The dragon tree - Hunt, Roderick; Brychta, Alex (United Kingdom : Oxford University press)
Biff, Chip, Kipper, and their dog Floppy are whisked away to a magical forest where they come face-to-face with a menacing dragon guarding a mysterious tree. The children must use their wits to outsmart the dragon and solve the mystery, making for an exciting and suspenseful adventure. This story is perfect for young readers, offering a blend of fantasy and problem-solving.
The adventure begins when Biff, Chip, Kipper, and Floppy use the magic key to enter a new world. They find themselves in an eerie forest where they encounter a fearsome dragon guarding a mysterious tree. The story unfolds as they work together to outsmart the dragon and return safely home. Key scenes include discovering the dragon, solving the mystery of the tree, and the thrilling escape.
Location: 1A
Keywords: Oxford Text-book